Systematic review and collaborative recalculation of 133 693 incident cases of schizophrenia. Issue 1 (January 2014) - van der Werf, M.; Hanssen, M.; Köhler, S.; Verkaaik, M.; Verhey, F. R.; RISE Investigators; van Winkel, R.; van Os, J.; Allardyce, J.
<x content-type="archive" xml:space="preserve">Abstract</x> Background This systematic review and collaborative recalculation was set up to recalculate schizophrenia incidence rates from previously published studies by age and sex. Method PubMed, EMBASE and PsycINFO databases were searched (January 1950 to December 2009) for schizophrenia incidence studies. Numerator and population data were extracted by age, sex and, if possible, study period. Original data were requested from the authors to calculate age- and sex-specific incidence rates. Incidence rate ratios (IRRs) with their 95% confidence intervals (CIs) were computed by age and sex from negative binomial regression models. Results Forty-three independent samples met inclusion criteria, yielding 133 693 incident cases of schizophrenia for analysis. Men had a 1.15-fold (95% CI 1.00–1.31) greater risk of schizophrenia than women. In men, incidence peaked at age 20–29 years (median rate 4.15/10 000 person-years, IRR 2.61, 95% CI 1.74–3.92). In women, incidence peaked at age 20–29 (median rate 1.71/10 000 person-years, IRR 2.34, 95% CI 1.66–3.28) and 30–39 years (median rate 1.24/10 000 person-years, IRR 2.25, 95% CI 1.55–3.28). This peak was followed by an age–incidence decline up to age 60 years that was stronger in men than in women (χ2 = 57.90, p < 0.001). The relative risk of schizophrenia was greater in men up to age 39 years and this reversed to a greater relative risk in women over the age groups 50–70 years. No evidence for a second incidence peak in middle-aged women was found. Conclusions Robust sex differences exist in the distribution of schizophrenia risk across the age span, suggesting differential susceptibility to schizophrenia for men and women at different stages of life.